Pengaruh Oversize Terakhir Cylinder terhadap Performance Engine Type KVY - Airlangga Putra; Permana, Tatang; Sukrawan, Yusep (Jurnal Kendali Teknik dan Sains, 2026)
Motorcycles are one of the main modes of transportation widely used by the Indonesian people due to their practicality, efficiency, and ability to support daily mobility. However, many motorcycle users complain about the suboptimal engine power, especially when the vehicle is used on extreme terrains outside urban areas, such as uphill roads, rocky paths, or long distances. This situation has driven the development of various innovations in the automotive field to improve engine performance. One widely applied method is the oversize technique on the piston and piston block, which aims to increase the combustion chamber capacity, thereby maximizing the power output. This study aims to analyze the significant comparison of engine performance after the application of the oversize method on the KVY engine type, as well as to examine the factors influencing the optimization of engine performance based on the philosophy and needs of the vehicle owner. The testing method used a dynamometer to measure the increase in torque and engine power. The test results showed that the daily oversize application resulted in a torque increase of 1.19 Nm and a power increase of 0.85 Hp compared to the standard condition. Meanwhile, the oversize for competition needs showed more significant improvements, with a torque increase of 7.97 Nm and a power increase of 8.12 Hp. These findings demonstrate that the oversize method can significantly enhance engine performance according to its intended use.